1995
DOI: 10.1172/jci118258
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset X-linked sideroblastic anemia. Missense mutations in the erythroid delta-aminolevulinate synthase (ALAS2) gene in two pyridoxine-responsive patients initially diagnosed with acquired refractory anemia and ringed sideroblasts.

Abstract: X-linked sideroblastic anemia (XLSA) is caused by mutations of the erythroid-specific 6-aminolevulinate synthase gene (ALAS2) resulting in deficient heme synthesis. The characteristic hypochromic, microcytic anemia typically becomes manifest in the first three decades of life. Hematologic response to pyridoxine is variable and rarely complete. We report two unrelated cases of highly pyridoxine-responsive XLSA in geriatric patients previously diagnosed with refractory anemia and ringed sideroblasts. A previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…Expression, Purification, and Enzymatic Activities of Wild Type and Mutant ALAS2-Large amounts of pure wild type and mutant ALAS2 were obtained for comparisons of properties, by expression of the enzymes as fusion proteins with the E. coli MBP (9). Previous studies in this laboratory had shown that expression of native human ALAS2 in bacteria resulted in large amounts of inclusion bodies but that the fusion protein with the attached highly soluble MBP was active and soluble, facilitating purification by amylose affinity chromatography.…”
Section: Identification Of a Novel Exon 11 Mutation In A Patient Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression, Purification, and Enzymatic Activities of Wild Type and Mutant ALAS2-Large amounts of pure wild type and mutant ALAS2 were obtained for comparisons of properties, by expression of the enzymes as fusion proteins with the E. coli MBP (9). Previous studies in this laboratory had shown that expression of native human ALAS2 in bacteria resulted in large amounts of inclusion bodies but that the fusion protein with the attached highly soluble MBP was active and soluble, facilitating purification by amylose affinity chromatography.…”
Section: Identification Of a Novel Exon 11 Mutation In A Patient Withmentioning
confidence: 99%
“…The severity of the disorder (neonatal to late onset) depends primarily on the amount of residual ALAS2 mitochondrial enzyme activity. Structural and functional studies of pure wild type and mutant ALAS2 have been facilitated using prokaryotic overexpression of a fusion protein to stabilize and solubilize the enzyme (8,9). Of all of the XLSA coding mutations, only p.Arg452Cys and p.Arg452His have been found to display normal ALAS2 enzymatic activity and thermostability in vitro, suggesting that some other factor reduced ALAS2 activity in vivo (10).…”
mentioning
confidence: 99%
“…4 However, the phenotypic expression of XLSA is highly variable, 5 and occasional patients, both males and females, may present late in life. 6,7 Distinctive laboratory features are microcytic anemia with hypochromic red cells, increased red cell distribution width and evidence of parenchymal iron overload: for a conclusive diagnosis of XLSA, however, identification of the ALAS2 mutation is required. The management of XLSA involves not only treatment of anemia, but also prevention and treatment of iron overload, family studies to identify additional at-risk individuals, and genetic counseling.…”
Section: X-linked Versus Autosomal Recessive Congenital Sideroblasticmentioning
confidence: 99%
“…Severity varies widely depending on the amount of residual enzymatic activity, with onset of anemia typically during youth but ranging from birth 3,8 to the ninth decade of life. 9,10 While probands are frequently males because of hemizygosity of the X-linked defect, females are occasionally affected, most likely because of skewed X-chromosome inactivation in favor of sparing the mutant allele. 9 The enzymatic reaction catalyzed by ALAS2 requires pyridoxal 5Ј-phosphate as a cofactor, and most published ALAS2 mutations have resulted in pyridoxine-responsive phenotypes as measured by consistent, even if slight, increases in hemoglobin (Hb) concentration following vitamin supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 While probands are frequently males because of hemizygosity of the X-linked defect, females are occasionally affected, most likely because of skewed X-chromosome inactivation in favor of sparing the mutant allele. 9 The enzymatic reaction catalyzed by ALAS2 requires pyridoxal 5Ј-phosphate as a cofactor, and most published ALAS2 mutations have resulted in pyridoxine-responsive phenotypes as measured by consistent, even if slight, increases in hemoglobin (Hb) concentration following vitamin supplementation. 5,7 This is particularly apparent if iron overload has been ameliorated by phlebotomy or chelation therapy.…”
Section: Introductionmentioning
confidence: 99%